PENGARUH HUKUM WARIS ISLAM TERHADAP HUKUM WARIS ADAT PADA MASYARAKAT GAYO (STUDI DI KABUPATEN ACEH TENGAH) - ADI FITRA (PREMISE LAW JURNAL, 2015)
Patah Titi law is the disconnection of cognates between grandfather/grandmother and their grandchildren because the father or the mother of the grandchild/ren died before the testator. In the traditional culture of Gayo, the beneficiary of this Patah Titi does not receive the property left by his/her grandfather/grandmother at all, and which is more painful is that the family relationship between the beneficiary/grandchildren and their grandfather’s family who experiences Patah Titi. It is true that there is no substitution in Islamic Law, but Islamic Law does not disconnect the cognates, even the grandchildren who have lost their parents still get their parts through grant although the amount they receive is small but they still receive inheritance from their grandfather. One of the concepts of Islamic InheritanceLaw Reform is the Compilation of Islamic law widely socialized through Presidential Instruction No.1/199. The Compilation of Islamic Law in its Article 185,  gives the right of a heir who has passed away to his/her descendants who are still alive. Keywords: Influence, Islamic Inheritance Law, Gayo Adat Inheritance Law